2005
DOI: 10.1074/jbc.m413590200
|View full text |Cite
|
Sign up to set email alerts
|

Filamin A Binding Stabilizes Nascent Glycoprotein Ibα Trafficking and Thereby Enhances Its Surface Expression

Abstract: The glycoprotein (Gp) Ib-IX-V complex is essential for platelet-mediated hemostasis and thrombosis. The cytoplasmic domain of its largest polypeptide subunit GpIb␣ possesses a binding region for filamin A, which links GpIb-IX-V to the platelet cytoskeleton. There is evidence that filamin A binding to GpIb␣ directs the surface expression of GpIb-IX. To investigate the mechanism of this effect, we examined GpIb␣ biosynthesis in Chinese hamster ovary (CHO) cells stably co-expressing wildtype or mutant GpIb␣ with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
1
22
1
Order By: Relevance
“…FlnA binding facilitates GPIb surface expression in Chinese hamster ovary (CHO) cells (Feng et al, 2005), and the interaction between FlnA and GPIb has been reported to influence VWF receptor function, although conflicting effects are found in the literature. CHO cells transfected with GPIb mutants that lack the FlnA binding site have decreased VWF binding (Dong et al, 1997;Schade et al, 2003), VWF-induced cell aggregation (Mistry et al, 2000), and/or adhesion to a VWF matrix under high shear (Cranmer et al, 1999;Williamson et al, 2002;Cranmer et al, 2005).…”
Section: Mild Thrombocytopenia In Female Mice Carriers For Flna Deficmentioning
confidence: 99%
“…FlnA binding facilitates GPIb surface expression in Chinese hamster ovary (CHO) cells (Feng et al, 2005), and the interaction between FlnA and GPIb has been reported to influence VWF receptor function, although conflicting effects are found in the literature. CHO cells transfected with GPIb mutants that lack the FlnA binding site have decreased VWF binding (Dong et al, 1997;Schade et al, 2003), VWF-induced cell aggregation (Mistry et al, 2000), and/or adhesion to a VWF matrix under high shear (Cranmer et al, 1999;Williamson et al, 2002;Cranmer et al, 2005).…”
Section: Mild Thrombocytopenia In Female Mice Carriers For Flna Deficmentioning
confidence: 99%
“…18 After transfection (72 hours) the cells were rinsed with phosphate-buffered saline (PBS) and lysed in PBS containing 1% Triton X-100, 1 mM phenylmethylsulfonyl fluoride (PMSF), 5 mM EGTA, 1 mM EDTA, 1 g mL Ϫ1 pepstatin A, 1 g mL Ϫ1 aprotinin, and 1 g mL Ϫ1 leupeptin. Cell lysates were centrifuged at 15 000g for 10 minutes.…”
Section: In Vivo Binding Assaymentioning
confidence: 99%
“…NMR spectroscopy confirmed that the double mutant caused no major defects in folding of the domain (data not shown). We also expressed GFP-tagged full-length human FLNa in the CHO-GPIb␣␤/IX cells that stably express GPIb␣␤/IX complex, 18 and were able to bring down FLNa with the GPIb␣␤/IX complex ( Figure 3C). Double-mutant (G1879D and C1912D) GFP-FLNa constructs expressed at levels equivalent to endogenous FLNa in CHO cells did not associate at all with GPIb␣␤/IX ( Figure 3C), confirming that IgFLNa17 is also the major GPIb␣-binding site in vivo.…”
Section: Point Mutations In Domain 17 Of Full-length Flna Disrupt Thementioning
confidence: 99%
See 1 more Smart Citation
“…16 The intracellular properties of the receptor have also been incriminated in defective platelet biogenesis in relation to the linkage of GPIb-V-IX to the submembranous actin cytoskeleton, which is mediated by filamin. 17 Actin reorganization, with the participation of PKCα, appears to be important for the formation of proplatelet extensions, but the involvement of a GPIb-actin link in this process has not been established. 18,19 Finally, as GPIb-V-IX is expressed at high density on the cell surface (24,000 copies/platelet), it could represent a membrane structuring element in the course of proplatelet formation.…”
Section: Introductionmentioning
confidence: 99%